Establishment of a reverse transcription recombinase-aided amplification detection method for porcine group a rotavirus - Wang, Yushun; Nie, Mincai; Deng, Huidan; Lai, Siyuan; Zhou, Yuancheng; Sun, Xiangan; Zhu, Ling; Xu, Zhiwen (Frontiers in Veterinary Science, 2022)
Porcine rotavirus type A (PoRVA) is the main cause of dehydrating and diarrhea in piglets, which has a great impact on the development of pig industry worldwide. A rapid, accurate and sensitive detection method is conducive to the monitoring, control and removal of PoRVA. In this study, a PoRVA real-time fluorescent reverse transcription recombinase-aided amplification (RT-RAA) assay was developed. Based on the PoRVA VP6 gene, specific primers and probes which were designed and synthesis. The sensitivity of this method was not much different than the real-time fluorescent quantitative PCR(RT-qPCR) for PoRVA, which was 7 copies per reaction. The results of RT-RAA and SYBR GreenⅠRT-qPCR methods were completely consistent in 110 clinical samples. Therefore, we successfully established a rapid and specific RT-RAA diagnostic method for PoRVA.